Development of a Mobile Health Application Based on a Mixed Prenatal Care in the Context of COVID-19 Pandemic - Rommy Helena Novoa; Luis Meza-Santibañez; Noe Rodríguez-Hilario; Juan Torres-Osorio; Vladimir Jáuregui-Canchari; Xin Huang-Yang; Wilder Eduardo Melgarejo; Juan Carlos Bazo-Alvarez; Walter Ventura (Revista Brasileira de Ginecologia e Obstetrícia, 2023)
Abstract Objective We describe the development and structure of a novel mobile application in a mixed model of prenatal care, in the context of the COVID-19 pandemic. Furthermore, we assess the acceptability of this mobile app in a cohort of patients. Methods First, we introduced a mixed model of prenatal care; second, we developed a comprehensive, computer-based clinical record to support our system. Lastly, we built a novel mobile app as a tool for prenatal care. We used Flutter Software version 2.2 to build the app for Android and iOS smartphones. A cross-sectional study was carried out to assess the acceptability of the app. Results A mobile app was also built with the main attribute of being connected in real-time with the computer-based clinical records. The app screens detail information about activities programmed and developed in the prenatal care according to gestational age. A downloadable maternity book is available and some screens show warning signs and symptoms of pregnancy. The acceptability assessment was mostly rated positively regarding the characteristics of the mobile app, by 50 patients. Conclusion This novel mobile app was developed as a tool among pregnant patients to increase the information available about their pregnancies in the provision of a mixed model of prenatal care in the context of the COVID-19 pandemic. It was fully customized to the needs of our users following the local protocols. The introduction of this novel mobile app was highly accepted by the patients.